Paths to apply the Open Strategy in local governments: The Umuarama Case - Paes de Vilhena, Renata Maria; Rabelo Ribeiro, Fernando; Ceranto Júnior, Edvaldo (Revista del CLAD Reforma y Democracia, 2025)
Created in 2006, the Umuarama Development Council, in the state of Paraná, Brazil, brings together members from various sectors with the aim of proposing policies for local development. After years of difficulties in mobilizing people, projects, and resources, in 2023 the Council decided to propose to the city government the creation of the Umuarama 2050 Plan, which had broad participation from society and the support of a specialized institution. Thus, among several institutions analyzed, the Council Plenary selected the Dom Cabral Foundation and recommended it to the municipal administration. As a member and partner of the Council, the city government designed a customized solution with the Foundation that involved the participatory construction of a long-term vision for the municipality. To this end, the project included interviews and focus groups; a participation platform with artificial intelligence; a public conference; and three governance groups, which were composed of different leaders involved at different times. This article aims to explore the role and effectiveness of each of these methodologies, considering the results achieved and how much they contributed to and influenced the strategy. Furthermore, it aims to illuminate the theoretical-practical debate on the construction of strategic planning for local development based on the engagement of different stakeholders.